The system of the United Nations depository libraries in the USSR - Balsytė, Raimunda (Knygotyra, 1986)
The system of the United Nations depository libraries, the differencies between the UN depository libraries and UN information centres libraries are discussed in the article. The main attention is paid to the creation of depository libraries of UN and its specialized agencies in the Soviet Union. The problems important to these libraries nowadays are treated too.